The Cultural implication of Gender Equity Policies in Academia - Warner, Racquel (International Journal of Educational Studies, 2025)
This study explores the intersection of gender equity policies in the education sector and their broader cultural implications, particularly in advancing Sustainable Development Goal 5 (SDG 5). Using a qualitative literature review methodology, this study synthesizes academic research, policy reports, and case studies to assess the effectiveness of institutional policies in fostering gender equity and driving cultural transformation. The analysis highlights how gender action policies contribute to increased female participation in STEM fields, enhance research quality, and promote diverse academic discourse. Moreover, it examines how these policies shape student aspirations and gender identities, influencing societal perceptions of gender roles. By identifying key themes and patterns within the literature, this study underscores the role of academic institutions as agents of systemic change. Findings suggest that well-designed gender equity strategies not only improve representation in education but also catalyze long-term cultural shifts toward greater inclusivity and equality. This research contributes to the ongoing discourse on gender equity by providing a critical examination of existing policies and their transformative potential in academic and social contexts.